Development of Arabic-Indonesian Android Dictionary for Madrasah Aliyah Students - Ramadhani, Muhammad Fakhry; Murtadho, Nurul; Irhamni, Irhamni; Ismail, Muhd Zulkifli (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
Corpus linguistics plays an important role in studying Arabic because it can collect Arabic data from various sources and analyse them comprehensively. This research aims to develop Arabic learning media in the form of an Arabic-Indonesian Android dictionary based on corpus linguistics for high school students that is valid and practical. The development model used is the development model of Richey & Klein. The results showed that the learning media of the Arabic-Indonesian dictionary based on corpus linguistics integrated Android application is valid and practical to be used in learning. The findings of this study not only underline the potential of dictionary learning media in the learning environment but also highlight the practical implications of incorporating this kind of media into the Arabic language curriculum to facilitate students in learning the language